Case Report: Combination oral appliance therapy acute influence on cardiac electrophysiology and hemodynamics in OSA patient with paroxysmal atrial fibrillation - Schramm, Preetam; Schneiderman, Emet; Hui, Jason; German, Zohre; Lin, Ju Ying (Frontiers in Sleep, 2025)
Background and objectivesSleep apnea-related autonomic responses may increase cardiac arrhythmias. Ablation, cardioversion, and pharmacologic therapies for paroxysmal atrial fibrillation (AF) could benefit from adjunctive oral appliance therapy with a mouth shield (OAT+) compared to auto-adjusting positive airway pressure (APAP).MethodsA 67-year-old male with moderate obstructive sleep apnea (OSA), AF history, three ablations, and on Carvedilol (10 mg daily) underwent home sleep recordings with APAP and with OAT+ after 4 weeks. Randomly selected premature atrial contractions (PACs; n=20) and time-linked plethysmography waves from each intervention were compared.ResultsOAT+ reduced the PAC index (-61.9%), cardiac conduction intervals (nR-R, p = 0.025; pre-PAC R-R, p = 0.003; R-PAC-R, p = 0.051; PAC R-post systolic pause-R, p < 0.001) except for a P-R interval increase (p = 0.032). PAC-associated plethysmography wave amplitudes increased with OAT+ (pre-PAC wave-1, p < 0.001; PAC wave-2, p = 0.023; post-PAC wave-3, p < 0.001).ConclusionsOAT+ shows promise as an adjunct AF therapy in OSA patients, improving cardiac conduction and vascular function over APAP.